Implementation of Islamic Religious Education Learning In Improving Students' Morals - Sa’adah, Sa’adah; Syafi’i, Imam; Khamim, Nur; Muid, Abdul (Chalim Journal of Teaching and Learning, 2023)
. The qualitative research approach is research that is descriptive and tends to use analysis. The process and meaning are more highlighted in qualitative research, the theoretical foundation is used as a guide so that the focus of research is following research facts. The qualitative approach centers on the description of the subject's perspective, process, and conceptual details of the subject. When these two methods deal with the same research theme, the natural environment is a direct source of data, humans are the main tool/instrument of data collection, and data analysis is carried out inductively.  Results: Results in general in scientific activities take a qualitative approach emphasizing the quality aspect of the quantity studied. Citing information on the Ministry of Education's website, the qualitative approach is an emic perspective. The purpose from an emic point of view is a form of qualitative research approach that uses data in the form of narratives, story details, expressions, and construction results from informants. Data can be obtained from data collection techniques in the form of in-depth interviews and observations.